Association of normal weight obesity phenotype with inflammatory markers: A systematic review and meta-analysis - Mohammadian Khonsari, Nami; Baygi, Fereshteh; Tabatabaei-Malazy, Ozra; Mohammadpoor Nami, Sahar; Ehsani, Amir; Asadi, Sasan; Qorbani, Mostafa (Frontiers in Immunology, 2023)
Background Individuals with normal weight could suffer from obesity based on their body fat percentage (also known as normal weight obesity (NWO)), thus being at risk of significant morbidity and mortality compared to the general population. It seems that inflammatory pathways and chronic inflammation are significant contributors to the pathogenicity of NWO. This study aimed to assess and pool the association of proinflammatory and anti-inflammatory cytokines with NWO. Methods In this systematic review and meta-analysis, online international databases (PubMed, Scopus, EMBASE, Web of Science, and Google Scholar) were searched until August 2022. All observational studies with an English full text comparing the mean levels of proinflammatory and anti-inflammatory cytokines (e.g., C-reactive protein (CRP), various types of interleukins (IL) s, tumor necrosis factor-alpha (TNF)) and white blood cell (WBC) count, in subjects with NWO and “normal weight non-obese (NWNO)” were included. Two researchers independently screened, reviewed and assessed the quality of included studies. The remaining articles' data were extracted post-screening. The heterogeneity between studies was assessed using the I2 and Cochran's Q tests. A random effect model meta-analysis was used to pool the standardized mean difference (SMD) as an effect size. Results From the initial 559 studies, 21 and 19 were included in the qualitative and quantitative synthesis, respectively. In the systematic review, 8 studies reported a significant association between various proinflammatory cytokines (CRP, IL6, IL1β, and TNFα) and NWO. According to random-effect meta-analysis, the association between NWO with CRP (SMD: 0.60, 95% CI: 0.30, 0.91) and IL6 (SMD: 0.90, 95%CI: 0.14, 1.66) was statistically significant. Moreover, the mean level of TNFα in subjects with NWO and NWNO did not differ significantly (SMD: 0.67, 95% CI: -0.36, 1.70). Conclusion The findings of this study show that NWO was associated with high levels of CRP and IL6. Therefore, inflammatory pathways may play a role in the pathogenicity of NWO.